Parenting Skill Training: Pelatihan Kemampuan Pengasuhan bagi Pengurus Pondok Pesantren Kanak-kanak Putra Darussalam Blokagung Banyuwangi - Sa'diah, Halimatus; Baroroh, Nurin; Anikoh, Indifatul; Karim, Abdul; Chintya Hilyatun Nisa’ (Keris: Journal of Community Engagement, 2024)
Character building in students in Islamic boarding schools is one of the important roles that continues to be carried out by caregivers, especially boarding school administrators. As a substitute element for the main caregiver, administrators have a central role in being able to monitor the development of students as a whole. Like the administrators of children's boarding schools, where administrators need basic skills in caring for children. Parenting training is needed to improve the knowledge and skills of boarding school administrators in caring for children in the boarding school environment. This service process uses a strategic approach with principles based on Asset Based Community-driven Development (ABCD). The important thing in the paradigm and principles of the ABCD approach is the context of understanding and internalizing assets, potential, strengths, and utilization that are carried out independently and optimally. The stages start from the program preparation stage, the program implementation stage, and the success stage of parenting training. As a result, the administrators of children's boarding schools benefit from understanding the phases of child development, related to physical, social, emotional, cognitive development, to personality development. The administrators are optimistic in developing a positive attitude towards students, including understanding how to communicate effectively. It is hoped that after this activity, the administrators will be able to increase awareness of the potential of good students in educating child students, so that the development of child students will be optimal.